Health Literacy in the Short Film Stunting “Konsumsi Bergizi Bikin Glowing” - Rifaqi, Dela Aufa; Adiprabowo, Vani Dias (GoAcademica Research & Publishing, 2024)
Indonesia is a developing country with a low health index, one of which is indicated by the high prevalence of stunting. Stunting is a growth disorder in children due to chronic malnutrition that has an impact on long-term physical and cognitive health. This study aims to explore the messages in the short film